Adapting to Service Quality; Building Public Trust through A Servqual Perspective - Setiawan, Heru (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This article aims to analyze the quality management of madrasah services in building public trust in MAN 1 Tanjung Jabung Barat, Jambi. Public trust is included in the critical components to be taken into account. This is because competition in education is also heavily influenced by public trust. This study uses a qualitative approach to the type of case study. Data collection techniques are carried out through observation, interviews and documentation. Data analysis was carried out by referring to the concept of Milles and Huberman, namely data collection, data reduction, data presentation and conclusion. The research results were five forms of service quality management at MAN 1 Tanjung Jabung Barat, Jambi, in building public trust: applicable vision and mission, responsive human resources, communication forums, professional teaching staff and adequate teaching infrastructure. This research has implications for building and maintaining public trust for the continuity of education in madrasahs.